Study of phase transitions induced by quenching and tempering heat treatment in 1045 steel - Trujillo, Alejandro (2023)
In this work we report the characterization of a sample of steel 1045 subjected to the thermal treatment of  quenching in water and quenching and tempering. The sample was made available by the Bholer,Company, Peru. Taking as reference the results of this characterization, the phase transformations that take place when a sample is subjected to the above mentioned treatments, are studied. The applied techniques were optical microscopy, dispersive Mössbauer spectroscopy and X ray fluorescence . The images by optical microscopy of the sample in its as received state, as “acero-ST”, reveals the presence of ferrite and perlite. The image of the sample quenched in water identified as ‘acero-agua’ reveals the presence of martensite; and the sample in the quenching and tempering state, denominated “acero –agua R” reveals the presence of the denominated tempered martensite. In addition, the measurements of hardness were carried out obtaining 219 HB, 634 HB and 525 HB for the samples acero-ST, acero-agua and acero-agua R respectively. The Mössbauer spectrum of the “acero-ST” sample exhibits two sextets associated to ferrite and perlite.  The Mössbauer spectrum for the sample “acero-agua” exhibits the presence of three magnetic sextets assigned to iron sites present in matensite,  that are occupied by the first three neighbors of each carbon atom. The Mössbauer spectrum that corresponds to the “acero-agua R” shows three magnetic sextets associated to annealed martensite.  In addition to iron, the X-ray fluorescence spectra of the samples under study show the presence of manganese, copper and chromium. We pretend that these obtained results will contribute to a better knowledge of the phase transformations that take place in Steel 1045 in the tempered in water and normalized states. Moreover, we look forward for better cooperation ties between the industrial and the academic sectors.